The application of the doctrine of 'Substance over form' as anti-avoidance mechanism by South African Income Tax Courts - Laubscher, V. E.(Vanessa Evelyn) (Stellenbosch : Stellenbosch University, 2012)
Assignment (M.Comm.) -- University of Stellenbosch, 1998.